Ontogenetic Dietary Shifts and Microscopic Tooth Wear in Western Chimpanzees - Stuhlträger, Julia; Schulz-Kornas, Ellen; Wittig, Roman M.; Kupczik, Kornelius (Frontiers in Ecology and Evolution, 2019)
Microscopic tooth wear studies on primates have largely focused on interspecific dietary comparisons, while few have addressed intraspecific variations such as those among age groups. Here, we examined to what extent dietary shifts during ontogeny can be revealed from microscopic tooth wear in a western chimpanzee population using 3D surface texture (3DST) analysis. To this end, we analyzed feeding observation data of 14 chimpanzees of the Taї National Park (Ivory Coast) and matched them to 3DST data analyzed on two wear facets (f9, f3) of deciduous fourth premolars and permanent molars of 41 specimens (infants, juveniles, adolescents, adults) of the same population. We expected to find an age-dependent increase in texture complexity resulting from the more frequent consumption of seeds and insects in older compared to younger individuals. Furthermore, we expected the introduction of phytolith-producing plants to the diet of post-weaned individuals to result in many small and parallel-orientated 3DST features in juveniles, adolescents and adults compared to infants. We found that the 3DST pattern did not mirror the observed increase in dietary breadth from infants to adults. However, we found that age-dependent differences in the consumption of phytolith-producing plants were reflected to some extent in the 3DST pattern: infants and adolescents who spent more time feeding on phytolith-producing plants than older individuals had more parallel orientated 3DSTs with higher peaks, while adults had flatter and more randomly orientated 3DST features. Our results suggest that phytoliths as small abrasive particles may be of greater importance for the 3DST formation than food categories such as fruits, leaves or seeds. However, compared to the variation in the feeding data, 3DST results show only little variation among age groups. We conclude that 3DST does not explicitly reflect ontogenetic dietary changes in chimpanzees. Rather, other factors, such as individual- or sex-based feeding habits as well as seasonal variation in dust accumulation, may be of greater importance for 3DST formation.